Mycobacterium microti Infection in Wild Boar (Sus scrofa): Histopathology Analysis Suggests Containment of the Infection - Pigoli, Claudio; Tranquillo, Vito; Gibelli, Lucia Rita; Gaffuri, Alessandra; Alborali, Giovanni Loris; Pacciarini, Maria; Zanoni, Mariagrazia; Boniotti, Maria Beatrice; Sironi, Giuseppe; Caniatti, Mario; Grieco, Valeria (Frontiers in Veterinary Science, 2021)
The European wild boar (WB) (Sus scrofa) population has rapidly expanded over the years, raising public health concerns over the species reservoir of several pathogens, including Mycobacterium microti (Mm), a Mycobacterium tuberculosis complex member. In this study, we aimed to investigate the Mm natural infection in WB in Lombardy and Emilia Romagna Italian regions by statistically evaluating the granulomatous lesions' histological features and Mm microbiological isolation. We analyzed 103 WB retropharyngeal and submandibular lymph nodes (LNs) for Mm identified by gyrB PCR-restriction fragment length polymorphism, and were retrospectively selected and histologically assessed. For each sample, Hematoxylin-eosin and Ziehl–Neelsen stained slides were evaluated. Considered histological variables were: the number of granulomas, size and maturational stage of granulomas, granulomas completeness within the section, number of multinucleated giant macrophages (MGMs), and acid-fast (AF) bacilli per granuloma. Furthermore, Mm microbiological results were also considered. Mm microbiological isolation was negatively influenced by granulomas maturation and positively affected by AF bacilli's presence within the section. Granuloma maturation was positively influenced by granuloma size and granuloma incompleteness and negatively affected by the number of granulomas in the section and the number of MGMs within the granuloma. The results indicate that granuloma maturation should ensures an efficient containment of Mm infection in the WB, suggesting that the intra-species transmission of the disease might be an unlikely event.